Antitumor efficacy of silver nanoparticles reduced with β-D-glucose as neoadjuvant therapy to prevent tumor relapse in a mouse model of breast cancer - Franco Molina, Moisés Armides; Reding Hernández, David; García Coronado, Paola Leonor; Kawas, Jorge R.; Zárate Triviño, Diana G.; Hernández Martínez, Sara Paola; Castro Valenzuela, Beatriz Elena; Rodríguez Padilla, Cristina (Frontiers in Pharmacology, 2024)
Neoadjuvant therapy constitutes a valuable modality for diminishing tumor volume prior to surgical resection. Nonetheless, its application encounters limitations in the context of recurrent tumors, which manifest resistance to conventional treatments. Silver nanoparticles (AgNPs) have emerged as a promising alternative for cancer treatment owing to their cytotoxic effects. This study systematically assessed the cytotoxic impact of beta-D-glucose-reduced AgNPs (AgNPs-G) both in vitro and as a neoadjuvant intervention against breast cancer cells within an in vivo model. These findings demonstrate that AgNPs-G diminishes the cell viability of the 4T1 cell line in a dose-dependent manner. However, in an ex vivo assay against a solid tumor, a higher dosage is required to achieve a commensurate effect observed in the in vitro assay. In an in vivo model examining the biodistribution of AgNPs-G in different organs and tumors, a heightened concentration of silver was detected in tumoral tissue. Moreover AgNPs-G reduced Ki67 and collagen expression, and no difference in the percentage of apoptotic cells in metastatic foci in lungs were found compared with the control. Consequently, intratumoral administration emerged as the optimal route for AgNPs-G delivery, mitigating potential adverse effects in other organs stemming from silver accumulation.